POTENSI TEMPURUNG KELAPA DAN KULIT JENGKOL SEBAGAI BAHAN ALTERNATIF BRIKET BIOPELLET DENGAN PEREKAT TEPUNG TAPIOKA UNTUK ENERGI TERBARUKAN - Dini Aulia Sari Ermal; Cici Maarasyid; Viona Aulia Rahmi; Lisa Legawati; Muhammad Yusri; Vriska Febiandini (Program Studi Kimia, Fakultas MIPA, Universitas PGRI Banyuwangi, 2026)
The global energy demand continues to rise, while dependence on fossil fuels such as LPG remains high, leading to resource depletion and increased greenhouse gas emissions. This study aims to explore the potential of coconut shell and jengkol peel as alternative raw materials for biopellet briquettes using tapioca flour as a binder, in support of renewable energy development. The methods included carbonization of raw materials, formulation of briquettes with varying ratios of coconut shell to jengkol peel (TK1 : KJ3, TK2 : KJ2, TK3 : KJ1) and binder concentrations (20%, 30%, 40%), followed by characterization based on moisture content, ash content, density, calorific value, compressive strength, and Energy Performance Index (EPI). Results showed that briquettes with a 2:2 ratio and 20% binder exhibited the best overall performance, with a calorific value of 11,794 cal/g, density of 0.987 g/cm³, moisture content of 7.258%, ash content 5,602 %, and an EPI of 1.604. These values meet or approach the Indonesian National Standard (SNI 01-6235-2000) for charcoal briquettes. The study concludes that coconut shell and jengkol peel are viable materials for biopellet production, offering a sustainable and environmentally friendly energy alternative.